Fresh/high-zinc maize: a promising solution for alleviating zinc deficiency through significant micronutrient accumulation - Rosales-Nolasco, Aldo; Molina Macedo, Aide; Leyva, Mayolo; San Vicente, Felix; Palacios-Rojas, Natalia (MDPI, 2023)
Zinc deficiency poses a significant health challenge worldwide, particularly in regions where access to and the affordability of dietary diversity are limited. This research article presents a time course analysis of kernel development on the zinc content in maize kernels with different genetic backgrounds, including normal maize, quality protein maize, and high-zinc maize, grown at two locations. Zn concentrations during stage I were high, decreasing between stages II and IV and increasing during stages V to VII. High-zinc kernel genotypes, including those ones with high-quality protein genetic backgrounds, have higher contents of zinc and iron during the milky stage (fresh/green maize). The zinc and iron content in fresh maize differed depending on the genotype. By consuming fresh maize biofortified with zinc, up to 89% and 100% of EAR needs can be fulfilled for pregnant women and children. The results demonstrate that fresh high-zinc maize accumulates a substantial amount of this micronutrient, highlighting its potential as a valuable source for addressing zinc deficiency.